PENGARUH NILAI TUKAR DAN PRODUK DOMESTIK BRUTO CHINA TERHADAP EKSPOR PISANG INDONESIA KE CHINA TAHUN 2004-2018 - Aprillia Dilla; Mardiana Mardiana; Darmayuda Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research aims to determine the Influence of the Exchange Rate And chinese GDP On Indonesian Banana Exports to China in 2004-2018. The variable used in the reseach is the Indonesian banana exports to china as the dependent variable, then the exchangerate and chinese GDP as an independent variable. This research uses secondary data in the form of time series in annual form starting from 2004-2018 which can be ontained through the publication of the Central Statistics Agency and the Ministry of Agriculture of the Republic of Indonesia. The model uses time series data which is calculated by the multiple linear regression method using the SPSS aplication version 23.0. The results of research indicate that partially the exchange rate variable has a significant positive effect on Indonesian banana exports to china in 2004-2018. Simutaneosuly , the Chinese exchange rate and GDP variable significantly influence the export of –Indonesian bananas to china in 2004-2018.Keywords :Export, Exchange rate, Chinese GDP